Fcγ Receptor Heterogeneity in Leukocyte Functional Responses - Rosales, Carlos (Frontiers in Immunology, 2017)
Antibodies participate in defense of the organism from all types of pathogens, including viruses, bacteria, fungi, and protozoa. IgG antibodies recognize their associated antigen via their two Fab portions, and are in turn recognized though their Fc portion by specific Fc gamma receptors (FcγR) on the membrane of immune cells. Multiple types and polymorphic variants of Fc gamma R exist. These receptors are expressed in many cells types and are also redundant in inducing cell responses. Crosslinking of Fc gammaR on the surface of leukocytes activates several effector functions aimed toward the destruction of pathogens and the induction of an inflammatory response. In the past few years, new evidence on how the particular IgG subclass and the glycosylation pattern of the antibody modulate the IgG-Fc gamma R interaction has been presented. Despite these advances, our knowledge of what particular effector function is activated in a certain cell and in response to a specific type of Fc gammaR remains very limited today. On one hand, each immune cell could be programmed to perform a particular cell function after Fc gamma R crosslinking. On the other, each Fc gamma R could activate a particular signaling pathway leading to a unique cell response. In this review, I describe the main types of Fc gama receptors and our current view of how particular Fc gamma receptors activate varios signaling pathways to promote unique leukocyte functions.